St. Augustine Wins Schools Panorama - Osman, Ruth (Express)
Youthful exuberance and the sweet sound of pan filled the northern greens of the Queen's Park Savannah in Port of Spain, during the National Junior Panorama Finals. In the end, top honours went to the St Augustine Senior Secondary Comprehensive Steelband (Under-21 category), who wowed the crowd with their "Band from Space".
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival)